FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERHASILAN PROGRAM INSEMINASI BUATAN (IB) PADA TERNAK SAPI POTONG - Supriyanto (Politeknik Pembangunan Pertanian Manokwari, 2016)
This study is based on the identification in Magelang found problems that Artificial Insemination Program (IB) does not work in some Ulib / Post IB sub district level, while the research objectives want to know the factors that influence the success of the IB program is not based on the value of the effectiveness of IB is NRR, CR and S/C. Sample or respondents came from inseminator and acceptor from Ulib with low efficiency and data values insemination program originated in the District Veterinary Office Magelang Metode primary and secondary data collection, secondary data obtained by the survey either come from the Office of the District and Sub-District, while the primary data derived of sample/ respondents by interview using questionnaires. The data obtained were analyzed descriptively to obtain figures NRR, CR and S/C. The results showed the IB program unsuccessful of all districts in Magelang with niai NRR = 37.75 %, the S/C = 2.85 and CR = 33.70 %. Inseminator Performance (88.60 %), Performance acceptor farmers (64.95 %), PTM test for sperm motility straw ± 78.50%, ± 85% live sperm, sperm die of ± 15 %, ± 24.6 sperm count million. Appearance livestock body condition with ≥ 5 (moderate and above) were 26 individuals (27.08 %), while livestock that have a thin body condition or with a score of less than <5 of 70 individuals (72.92 %). Conclusion failure AI programs likely due to the performance of farmers (64.95%) and BCS <5 (skinny) ± 72.92%.